Leveraging Digital Library to Enhance Research and Learning Experience of College Students: An In-Depth Study - Chunying Yang (Journal of Mathematics)
A digital library is a platform that contains collections of books, services, and personnel to support the sharing of knowledge with creation, dissemination, and preservation. In this context, any university library should comprehensively embrace the developmental trend occurring in the library setting, which should be strictly followed by university libraries as a special mission. Digital libraries should also actively promote the updating of the embedded service model and further upgrade the various resources of the university library. Thus, the digital library provides a platform to assist students to develop an inclination towards learning and emotional shaping. Its functional system thus serves both comprehensive and harmonious development of students. Especially, the knowledge service module of the digital library incorporates users’ scientific research context. Most of the existing research studies focus on the individual researcher and neglects the context of the entire research team. Knowledge recommendation for the context of team-based scientific research activities can better serve more scientific research activities and team cooperation. In this work, we propose a knowledge recommendation algorithm for digital libraries based on team research-knowledge application in context matching. We leverage the context-aware learning model to construct the corresponding application context of the digital library knowledge and the context model of team scientific research. Subsequently, we select alternative knowledge and neighbor users as active users and further complete knowledge sorting and recommendation. According to the knowledge recommendation system in a digital library, it is confirmed that the proposed method can effectively deliver the knowledge of researchers in the context of the digital library.